Aplicación web para el procesamiento de información del observatorio socioeconómico de Cotopaxi . - Macas Angulo, Darwin Lenin (2020)
The present work is part of the researching project "Socio-Economic Observatory of Cotopaxi", which belongs to the Administrative Sciences Major in the Technical University of Cotopaxi, and whose objective is to measure the socio-economic impact in Latacunga Canton, through the collection of data through a survey of nine sections that add up to 43 items. The major of Engineering in Computer Science and Computer Systems contributes to this project through the development and placement of a Web Application for the processing and results of the data obtained from the survey (1393 respondents), the work has been adjusted to the needs raised by the coordinators of the project, so that it allows to obtain statistical reports automatically and download the required information. For the development of the application, the following free software tools were used: Django, Python, PostgreSQL; in addition, the Prototype-Evolutionary model was applied, which allowed, through the execution of its different phases, to obtain a first test product to later refine the functionalities, until arriving at an engineering software, which is the one delivered to the final user. The application is currently in production, working with real data, which allows to determine the fulfillment of the proposed objectives for this part of the work; later new functionalities will be implemented depending on the future requirements of the Socioeconomic Observatory.